The Antimicrobial and Antioxidant Activity of Endophytic Fungi Extract Associated with Chlorantus officinalis Blume and Staurogyne elongata Kuntze - Listiana Oktavia; Evana Evana; Muhammad Ilyas; Andria Agusta (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2020)
An endophytic fungi has been widely known for a source of bioactive compounds attributed as antimicrobial and antioxidant. In this report, we investigated the antimicrobial and antioxidant activity of extract of endophytic fungi associated with two indigenous Indonesian medicinal plants, i.e., Chloranthus officinalis (CO) and Staurogyne elongata (SE). Ten endophytic fungi isolates were collected from barks, roots, and leaves of CO and SE host plants and were cultured into potato dextrose broth (PDB) media. After 14 days of incubation, the whole culture was extracted by ethyl acetate. The qualitative antimicrobial analysis that was conducted by dot blot and TLC-bioautography showed all of the extracts show antimicrobial activity against Staphylococcus aureus. At the same time, they were observed less active against Escherichia coli. The minimum inhibitory concentration (MIC) analysis showed that endophytic fungi extract of CO2 and SE3 are classified as strong antibacterial activity against S. aureus with MIC value <8 µg/ml. The TLC bioautography of antioxidant displayed the appearance of radical inhibition area from SE4 and SE5 extract. Quantitative antioxidant activity, which was conducted by the radical DPPH scavenging, showed that SE5 has the lowest IC50 value, i.e., 56.3679 µg/ml (AAI value 0.5455) and was classified as moderate antioxidant activity. Meanwhile, the remaining extracts are classified as weak antioxidant activity.